The glucose-potassium ratio as a marker of adverse prognosis in patients with chronic heart failure - Syvolap, V. V.; Lysenko, V. A.; Сиволап, Віталій Вікторович; Лисенко, Владислав Андрійович (Запорізький державний медико-фармацевтичний університет, 2025)
The glucose-potassium ratio (GPR) has previously proven its prognostic role in acute pathological conditions: ischemic and hemorrhagic strokes, aortic aneurysm and dissection, myocardial infarction. However, changes in the serum GPR in patients with chronic heart failure (CHF) with preserved left ventricular ejection fraction (HFpEF) remain unclear. It is known that tubulointerstitial injury occurs in patients with CHF. The renal tubulointerstitium plays a leading role in the reabsorption of glucose, potassium, and sodium. Therefore, impaired glucose-potassium ratio in patients with CHF is expected. Aim. To examine changes in the glucose-potassium ratio in patients with ischemic HFpEF and to determine its impact on the short-term (1 year) prognosis. Materials and methods. The study involved 57 patients (men – 43.9 % (n = 25); women – 56.1 % (n = 32)) with ischemic CHF, stage II A–B, NYHA FC II–IV, 49.1 % (n = 28) with sinus rhythm, and 50.9 % (n = 29) with atrial fibrillation (AF). Patients with sinus rhythm and AF were comparable in age (p = 0.968), height (p = 0.167), weight (p = 0.539), BMI (p = 0.774), body surface area (p = 0.296). The serum GPR was calculated as the serum glucose level divided by the serum potassium level. ROC analysis and logistic regression analysis were performed. Results. According to the univariate regression model, an increase in the GPR above 1.1697 increased the number of adverse cardiovascular events by 11.15 times at the end of the 1st year of follow-up (95 % CI 1.33–93.50, p = 0.0048). Conclusions. Chronic heart failure with preserved left ventricular ejection fraction is accompanied by impaired tubulointerstitial function, which is confirmed by an increase in the glucose-potassium ratio, and its increase above 1.1697 (sensitivity 88.9 %, specificity 60.8 %) is associated with 11.15 times (p = 0.0048) higher odds ratio of adverse cardiovascular events within a year. Показано прогностичну роль глюкозо-калієвого відношення (ГКВ) у сироватці крові при гострих патологічних станах: ішемічних і геморагічних інсультах, розшарувальній аневризмі аорти, інфаркті міокарда. Втім, зміни відношення глюкоза / калій у сироватці крові в пацієнтів із хронічною серцевою недостатністю (ХСН) зі збереженою фракцією викиду залишаються нез’ясованими. Відомо, що у хворих на ХСН відбувається ураження тубулоінтерстицію. Тубулоінтерстицію нирок належить провідна роль у реабсорбції глюкози, калію, натрію. Отже, очікуваним є порушення ГКВ у хворих на ХСН. Мета роботи – дослідити зміни глюкозо-калієвого відношення у хворих на ХСН ішемічного ґенезу зі збереженою фракцією викиду лівого шлуночка та з’ясувати його вплив на наближений (1 рік) прогноз. Матеріали і методи. До дослідження залучено 57 хворих (25 чоловіків – 43,9 %; 32 жінки – 56,1 %) на ХСН ішемічного ґенезу, II А–Б стадії, II–IV ФК за NYHA. З поміж обстежених – 28 (49,1 %) пацієнтів із синусовим ритмом, 29 (50,9 %) – із фібриляцією передсердь. Хворі з синусовим ритмом і фібриляцією передсердь зіставні за віком (р = 0,968), зростом (р = 0,167), масою тіла (р = 0,539), ІМТ (р = 0,774), площею поверхні тіла (р = 0,296). ГКВ у сироватці крові обрахували, поділивши показник глюкози в сироватці крові на рівень калію в сироватці крові. Здійснили ROC-аналіз і логістичний регресійний аналіз. Результати. За даними уніваріантної регресивної моделі, підвищення глюкозо-калієвого відношення понад 1,1697 збільшувало кількість несприятливих серцево-судинних подій на кінець першого року спостереження в 11,15 раза (95 % ДІ 1,33–93,50, р = 0,0048). Висновки. ХСН зі збереженою фракцією викиду лівого шлуночка супроводжується порушенням функції тубулоінтерстицію, що підтверджено зростанням глюкозо-калієвого відношення, а збільшення ГКВ понад 1,1697 (чутливість – 88,9 %, специфічність – 60,8 %) асоціюється з підвищенням відношення шансів несприятливих серцево-судинних подій упродовж року в 11,15 раза (р = 0,0048).
Глюкозо-калієве відношення як маркер несприятливого прогнозу в пацієнтів із хронічною серцевою недостатністю
Keywords: chronic heart failure with preserved ejection fraction; tubulointerstitial injury; glucosepotassium ratio; хронічна серцева недостатність зі збереженою фракцією викиду лівого шлуночка; ураження тубулоінтерстицію; глюкозо-калієве відношення